Women's Leadership in The Healthcare Sector - Ficka Vitriya; Nike Septembriana (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2022)
Women are underrepresented in healthcare leadership, yet there is no evidence of effective organizational strategies, practices, or policies that help women develop their careers. We want to look into this across industries to see how far women have come in terms of leadership in healthcare. The literature study identified two major themes: impediments to women's leadership and methods to expand women's leadership positions in the health sector. Socio-cultural hurdles, work-life conflicts, sexual harassment, gender disparities, and a lack of networks and role models for women leaders are all examples of these impediments. Furthermore, the process in the administration and organization of health, as well as unique career development programs for women, are all part of the goal to strengthen the leadership role of women in the health sector. This study lays out the evidence supporting organizational strategies to promote women in leadership in several settings, with implications for health care. It focuses on organizational transformation rather than people, documenting observable improvement across intervention areas. This work directly informs national efforts with international ties, allowing women to fulfill their professional aspirations in health care and move beyond obstacles to solutions.